The Percentage of Total and Regional Fat Is Negatively Correlated with Performance in Judo - Izabela Aparecida dos Santos; Gabriel Felipe Arantes Bertochi; Wonder Passoni Higino; Marcelo Papoti; Enrico Fuini Puggina (MDPI AG, 2023)
This study investigated the associations between total and regional body composition with performance in the special judo fitness test (SJFT), as well as strength and power tests (countermovement vertical jump-CMJ, squat jump-SJ, plyometric push-up-PPU, and force push-up-FPU). Twenty-three high-level judo athletes participated in this study. Initially, they underwent dual-energy X-ray absorptiometry, after which they performed the CMJ, SJ, PPU, and FPU tests. On another day, the SJFT was carried out. Correlations were tested using Pearson's test. The performance in the SJFT was correlated with the total and arm %fat mass (r = −0.759), torso fat mass (r = −0.802), torso %fat mass (r = −0.822) and in the lower limb regions with the leg fat mass (r = −0.803) and leg %fat (r = −0.745). In the strength and power tests, there were also negative correlations observed between regional fat and performance. There was a negative correlation between the percentage of total fat and performance in the SJFT (r = −0.824), SJ (r = −0.750), CMJ (r = −0.742), PPU (r = −0.609), and FPU (r = −0.736). Fat, both total fat and regional fat in the arms, torso, and legs, is strongly correlated with a poor performance in the SJFT and poor strength and power.